Die Übersetzung des Genfer Katechismus (1542/1545) ins Deutsche durch Zacharias Ursinus im Jahr 1563 - Neuser, Wilhelm H. (Koers, 2009)
The translation of the Genevan Catechism (1542/1545) into German by Zacharias Ursinus in 1563 It is with considerable surprise that one finds in the “Opera Selecta Calvini” vol. 2 a German translation of Calvin’s Geneva Catechism (1542/1545). The translation dates from 1563, and originated in Heidelberg. Even more surprising is the translator – none other than Zacharias Ursinus, one of the chief com-posers of the Heidelberg Catechism, which was also penned in 1563. The impression could be created that Calvin’s Catechism was intended at the outset to achieve the position later attained by the Heidelberg Catechism. The title of the German translation of Calvin’s Catechism is also interesting: “Catechism of the protestant churches in France”. Olevianus explained in a letter to Calvin that the translation was titled thus for fear that the Germans would otherwise not read the catechism. Comparing the German translation with the Geneva Catechism, it is evident that Ursinus made use of the French edition of 1542 as well as the Latin edition of 1545 as the source text. While his translation is literal, a few alterations in meaning occur, giving rise to decisive theological adjustments. A comparison with the Heidelberg Catechism is complicated by the fact that Ursinus was only one of a committee of composers who worked on the latter document. The theological corrections made to Calvin’s Catechism in the German edition reveal Ursinus’ tendency to emphasise the soteriological meaning in his translation. Beza would eventually be the one who would irreversibly modify Calvin’s theology in the direction of the reformed orthodoxy.